A COMPARATIVE STUDY ON PRIVATE AND PUBLIC HIGH SCHOOLS’ PRINCIPAL LEADERSHIP AND ITS IMPACT TO THE STUDENTS ACHIEVEMENT IN MATHEMATICS, SCIENCE AND ENGLISH SUBJECTS - Bahala, Ezhra B; Onrubia, Rene P; Bernal, Lorraine; Madrigal, Patricia Mae; Adan, John Edwardson (PEOPLE: International Journal of Social Sciences, 2018)
The study aims to understand the relationship between the principal’s leadership style of both public and private high school institutions and student’s performance in Math, Science and English. Support was found in a Theoretical model: Principal leadership effects on student’s learning growth in Mathematics (Dumay, Boonen, and Dame, 2013) which reinforces the relationship between principal leadership and student achievement.For this study, the researchers aim to focus on three hypotheses: identification of the difference between the teacher’s perception of the principal leadership style between private and public high school; the effects of such leadership styles and variables to the student achievement in each of the three general subjects (Mathematics, English, and Science); the effects of the dominant characteristics to the student achievements in general. Fifty-three teachers, both from private and public institutions, were administered the Multifactor Leadership Questionnaire 5X-Short form (MLQ 5X-Short). This measured all nine leadership characteristics and identified which type of leadership was dominantly displayed by their principal, for each school type. The study also examined the self-assessment of the principals for each school type and compared it to the perceptions of the teachers towards their leadership styles.Most findings were consistent with existing literature. In addition, this study also identified several areas of further study.